Treatment Results of Chronic Hepatitis C Genotype 5 and 6 Infections in Germany - Mauss, S.; Berger, F.; Vogel, M.; Pfeiffer-Vornkahl, H.; Alshuth, U.; Rockstroh, J. K.; Niederau, C.; Hüppe, D. (Zeitschrift für Gastroenterologie, 2012)
Chronic hepatitis C due to HCV genotype 5 and 6 infection is infrequently reported and patients are usually not included in trials. As boceprevir and telaprevir are not approved for these genotypes, pegylated interferon plus ribavirin will remain the treatment of choice for the coming years. Patients infected with HCV genotype 5 or 6 were identified by data base search from an ongoing observational cohort study in Germany. Of the total 23 893 patients, 39 patients (0.2 %) carried a HCV genotype 5 and 39 patients a HCV genotype 6 (0.2 %). Compared to other genotypes patients with genotype 5 were older and more often had a history of blood transfusion. Patients with genotype 6 were more often Asian and showed higher baseline alanine transaminase. Therapy with pegylated interferon alfa-2a and ribavirin was initiated in 24 patients with HCV genotype 5 and 27 patients with HCV genotype 6. After completion of 48 weeks of therapy an end of treatment response was achieved in 79 % and 81 % of treated patients, respectively. Sustained virological response was achieved in 58 % of patients with genotype 5 and in 59 % genotype 6 patients. HCV genotype 5 and 6 infections are rare in Germany. Our findings suggest that most HCV genotype 6 infections are seen in migrants from Asia, whereas HCV genotype 5 infections seem more due to spontaneous local infections. Sustained virological response seems to be better than for patients with genotype 1 or 4 with similar treatment duration.
Keywords: viral hepatitis; hepatitis C; HCV genotype 5; HCV genotype 6; HCV therapy